371. Risk Factors for Non-Albicans Candidal Vulvovaginitis. (26th November 2018) - Tressler, Andrea Boyd; Fortin, Chelsea; Radeva, Milena; Goje, Oluwatosin
Abstract: Background: Every year millions of women experience vulvo-vaginal candida. While the majority of the women with vulvo-vaginal candida are infected with albicans, the distribution of non-albicans candida (NAC) species varies depending on geography, race and ethnicity, and past medical history. While there are studies that explore the relationship between these factors and the incidence of NAC many of these studies are outdated. In this study, we explore the clinical risk factors for development of NAC compared with the more common albicans candida infections. Methods: We performed a retrospective cohort study. 174 women with a positive candida culture were identified via a database maintained by the Cleveland Clinic Microbiology department. Exclusion criteria were women with negative cultures, those under the age of 18, or with an initial encounter prior to 2004. Results: The average age of women who presented with NAC was 41.5 [31.0, 53.0] and was not statistically significant from women with no NAC, 43.0 [42.0, 45.0] ( P = 0.19). Among all initial positive yeast cultures 34.5% were C. glabrata followed by C. parapsilosis at 3.4%. Women who had a positive NAC culture were more likely to be post-menopausal than those with no NAC, 73.8 NAC vs. 26.2 no NAC ( P ≤ 0.001). Additionally, women cultured with NAC were more likely to be on hormone replacement therapy, 77.8 NAC vs. 22.2 no NAC ( P = 0.011). However, we found that recent antibiotic use, diabetes, and probiotic use had no impact. Conclusion: This study shows that post-menopausal women and women who are hormone replacement therapy are more likely to be colonized by NAC indicating that these are risk factors. Disclosures: All authors: No reported disclosures.